Changes in the testicular capsule and peritubular boundary tissue in pre-pubertal, pubertal and adult Japanese quails (Coturnix Coturnix Japonica) - Madekurozwa, Mary-Catherine (University of Pretoria, 2024)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2019.